Oxford handbook of emergency medicine - Jonathan P. Wyatt; Taylor, Robert G.; Wit, Kerstin de; Hotton, Emily J. (Oxford University Press, 2020)
Now in its fifth edition, the Oxford Handbook of Emergency Medicine is the essential rapid-reference guide to emergency medicine for everyone from junior doctors to specialist registrars, nurse practitioners, and paramedics. New and improved, the Handbook has been thoroughly revised throughout, with 100 extra illustrations and the latest guidelines and treatment advice, completely overhauled chapters on Medicine, Obstetrics and Gynaecology, and Paediatric emergencies, and new topics on treatment escalation, end-of-life care, and sepsis. Clear and concise, extensively updated, and packed with a host of new X-rays to aid identification and treatment, this Handbook has everything you need to thrive in the demanding world of emergency medicine today.